2009
DOI: 10.1088/0004-637x/705/1/l67
|View full text |Cite
|
Sign up to set email alerts
|

THE DEPENDENCE OF STAR FORMATION RATES ON STELLAR MASS AND ENVIRONMENT AT z ∼ 0.8

Abstract: We examine the star formation rates (SFRs) of galaxies in a redshift slice encompassing the z = 0.834 cluster RX J0152.7-1357. We used a low-dispersion prism in the Inamori Magellan Areal Camera and Spectrograph (IMACS) to identify galaxies with z AB < 23.3 mag in diverse environments around the cluster out to projected distances of ∼ 8 Mpc from the cluster center. We utilize a mass-limited sample (M > 2 × 10 10 M ⊙ ) of 330 galaxies that were imaged by Spitzer MIPS at 24 µm to derive SFRs and study the depend… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

29
156
11
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(197 citation statements)
references
References 30 publications
29
156
11
1
Order By: Relevance
“…The situation is different in clusters found so far at z < 1.4, where active star-forming galaxies preferentially reside in the cluster outskirts (e.g. Balogh et al 2004;Lidman et al 2008;Patel et al 2009). However, it is expected that more distant galaxy clusters contain a larger number of star-forming galaxies in their central regions (e.g.…”
Section: Introductionmentioning
confidence: 59%
“…The situation is different in clusters found so far at z < 1.4, where active star-forming galaxies preferentially reside in the cluster outskirts (e.g. Balogh et al 2004;Lidman et al 2008;Patel et al 2009). However, it is expected that more distant galaxy clusters contain a larger number of star-forming galaxies in their central regions (e.g.…”
Section: Introductionmentioning
confidence: 59%
“…In the high-z universe, some studies found similar results (e.g., Patel et al 2009;Feruglio et al 2010), but there are also hints for an opposite trend (i.e. increasing SFRs or star-forming galaxy fractions with increasing the background density) known as the reversal of SFR-density relation (e.g., Elbaz et al 2007;Popesso et al 2011a,b).…”
Section: Fig 6 Same Asmentioning
confidence: 86%
“…The SFR in their study is the "median" SFR in a given mass bin, which is different from the spatially "averaged" SFR of the nearby galaxies in Elbaz et al (2007) and Cooper et al (2008). Patel et al (2009) argue that the contradictory results may be caused by the different environment that they investigate and by the different sample selection. They observed the central region of galaxy clusters (that is not well resolved by the other studies).…”
Section: Introductionmentioning
confidence: 86%
“…For example, Elbaz et al (2007) used the GOODS data and find that the SFR-density relation observed locally is reversed at z ∼ 1, in the sense that the "average" SFR of galaxies over a given volume increases with the local galaxy density (see also Cooper et al 2008;Ideue et al 2009;Tran et al 2010). In contrast, Patel et al (2009) observed the galaxies in a galaxy cluster (RX J0152.7−1357) at z = 0.834 and find that the SFR-density relation at that redshift is not similar to those in Elbaz et al (2007) and Cooper et al (2008), but is similar to the one in the local universe (see also Feruglio et al 2010). The SFR in their study is the "median" SFR in a given mass bin, which is different from the spatially "averaged" SFR of the nearby galaxies in Elbaz et al (2007) and Cooper et al (2008).…”
Section: Introductionmentioning
confidence: 99%